THE EFFECT OF GIVING PINEAPPLE PEEL EXTRACT (Ananas comocus L.Merr) IN DRINKING WATER ON ABDOMINAL FAT IN JOPER CHICKEN - ., Nurhafidah; Candrawati, D. P. M. A.; Sriyani, N. L. P. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the effect of pineapple peel extract (ananas comocus L.Merr) in drinking water on bearing fat, mesentery fat, ventricular fat and abdominal fat in joper chickens. The design used in this study was a completely randomized design (CRD) with 4 treatments and 5 replications. Each cage unit was filled with 3 joper chickens which were 2 weeks old with homogeneous body weight. The four treatments were chickens that were given drinking water without treatment as a control (P0), chickens that were given drinking water with 6% pineapple peel extract (P1), chickens that were given 8% drinking water with pineapple peel extract (P2), chickens that were given drinking water with 10% pineapple peel extract (P3). The variables observed in this study were pad fat, mesentery fat, ventricular fat and abdominal fat. The results showed that joper chickens were given pineapple peel extract with treatments P1, P2 and P3 which did not give significantly different results (P>0.05) compared to P0 (control). Based on the results of the study it can be concluded that giving pineapple peel extract at a rate of up to 10% through drinking water has the same effect as the control on the percentage of abdominal fat.